2019
DOI: 10.4018/ijdet.2019070102
|View full text |Cite
|
Sign up to set email alerts
|

Study of Augmented Reality Applications Use in Education and Its Effect on the Academic Performance

Abstract: Augmented reality (AR) applications can be used in almost all education and training environments. In this study, it reveals the relationship between perceived usefulness, utility and attitudes regarding the use of AR applications in educational environments as well as the relationship between attitude levels and academic achievements. It also reveals the effect of AR application use on academic achievement in education. According to the findings obtained in the study, the followings have been found: the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Positive outcomes such as shorter completion time, motivation to complete experiments, and willingness to attend laboratory sessions were observed. In the classroom setting, Wahyu et al [78] observed improved scientific literacy among elementary students, with the same observed amongst undergraduate students by Lamb et al [79], and Kaya and Bicen [80].…”
Section: Ar In Physics Education Researchmentioning
confidence: 68%
“…Positive outcomes such as shorter completion time, motivation to complete experiments, and willingness to attend laboratory sessions were observed. In the classroom setting, Wahyu et al [78] observed improved scientific literacy among elementary students, with the same observed amongst undergraduate students by Lamb et al [79], and Kaya and Bicen [80].…”
Section: Ar In Physics Education Researchmentioning
confidence: 68%
“…[23] conclude that the implementation of AR in mathematics can increase students' motivation level. Also, [24] indicate that AR can promote learning achievement. Meanwhile, AR can also increase maths proficiency for students with disabilities [25].…”
Section: How Ar Enhances the Mathematics-learning Process?mentioning
confidence: 99%
“…In Kaya and Bicen's (2019) study, augmented reality applications were used in almost all educational and training environments [11]. In this study, applications of augmented reality in educational environments of use perceived usefulness, attitudes and the relationship between benefits, as well as the relationship between attitude and academic achievement levels is intended to applications related to augmented reality in educational environments, and as a result, students' attitude levels are strongly and positively perceived with ease; they have reached the results that it has an effect on attitude levels and academic success.…”
Section: Related Researchmentioning
confidence: 99%